2013
DOI: 10.1098/rsta.2012.0304
|View full text |Cite
|
Sign up to set email alerts
|

Principles of molecular assemblies leading to molecular nanostructures

Abstract: Self-assembled physisorbed monolayers consist of regular two-dimensional arrays of molecules. Two-dimensional self-assembly of organic and metal–organic building blocks is a widely used strategy for nanoscale functionalization of surfaces. These supramolecular nanostructures are typically sustained by weak non-covalent forces such as van der Waals, electrostatic, metal–ligand, dipole–dipole and hydrogen bonding interactions. A wide variety of structurally very diverse monolayers have been fabricated under ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 70 publications
1
34
0
Order By: Relevance
“…The estimation of the ''dewetting'' term is the most difficult. 1,2,20,25 In some cases, these polymorphs can be traced to differing amounts of coadsorption of solvent. Thus, the heats of wetting for the solvent on the substrate are overestimates of the net result of the multistep step ''dewetting''.…”
Section: Measurement or Calculation Of Thermodynamic Functions For Momentioning
confidence: 99%
See 2 more Smart Citations
“…The estimation of the ''dewetting'' term is the most difficult. 1,2,20,25 In some cases, these polymorphs can be traced to differing amounts of coadsorption of solvent. Thus, the heats of wetting for the solvent on the substrate are overestimates of the net result of the multistep step ''dewetting''.…”
Section: Measurement or Calculation Of Thermodynamic Functions For Momentioning
confidence: 99%
“…[1][2][3][4][5][6] To date, most variable temperature and composition STM studies at the solid-solution interface have been performed with home made or commercial instruments using heated (only) samples. Molecular self-assembly from solution onto surfaces is widely embraced as a strategy for creating adlayers with desirable electronic, photonic, and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 This adsorption mechanism will define the chemical reactivity of the precursor molecules on a specific surface determining the properties and the structure of the final outcome. 12 To date, some studies have been already reported to demonstrate a different behavior of the same molecule adsorbed on different surfaces, highlighting the role of the surface in the process. Examples of this observed behavior are the cases of perylenetetracarboxylic dianhydride (PTCDA), benzene, and porphyrins, among others, in which different properties have been observed as a consequence of the different geometrical adsorptions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The challenging stage for the drop-casting production of chiral solid films is surely the identification of the proper solvent to use for the stock solution. As reported in the literature, the nature of the solvent used is extremely relevant to define the structures that the layers adopt and the overall chirality (Iavicoli et al, 2009;Chen et al, 2019), since both derive from a combination of the interaction strength of the molecules with the surface and their solubility (Zaera 2009;Mali and De Feyter, 2013). Moreover, solvent parameters like viscosity, surface tension, and vapor pressure strictly impact the film adhesion to the substrate and the evaporation rate, producing layers featuring different structural motifs and homogeneity (Resedean et al, 2020).…”
Section: Evaluation Of the Solvent Effect On The Chirality Of The Filmmentioning
confidence: 99%